Comparison of plasma homocysteine levels in patients with type 2 diabetes mellitus with normal subjects - Kemal Gündüz (Journal of Clinical and Experimental Investigations, 2012)
Objectives: To compare the plasma homocysteine levelsbetween control group and diabetic patients with no diabeticretinopathy, with preproliferative diabetic retinopathy,with proliferative diabetic retinopathy.Materials and methods: Plasma homocysteine levels of23 diabetic patients were measured and were comparedwith 25 age-matched controls with no systemic problemand no ocular disease. Plasma homocysteine levels weremeasured using high-performance liquid chromatography.Results: Diabetic patients were divided into three groupsaccording to their ophthalmological findings. There were8 patients with no diabetic retinopathy, 8 patients withpreproliferative diabetic retinopathy, 7 patients with proliferativediabetic retinopathy. Plasma homocysteine levelswere higher in diabetic patients (13.30±4.03 μmol/L)compared to the control group (11.71±3.41 μmol/L) but nostatistically significant difference was found between thetwo groups (p>0.05). Plasma homocysteine levels weremeasured 12.50±3.73 μmol/L in no diabetic retinopathygroup, 12.90±2.59 μmol/L in preproliferative diabetic retinopathygroup, 14.64±5.69 μmol/L in proliferative diabeticretinopathy group. In diabetic group, plasma homocysteinelevels increased with the increase of the severityof retinopathy but not reached statistically significance(p>0.05).Conclusion: Although no statistically significance wasfound, retinopathy progresses with the increase of plasmahomocysteine levels. This can be used for the followupof the diabetic patients but further evaluation in largegroups is needed. J Clin Exp Invest 2012; 3(2): 235-239